Vous êtes sur la page 1sur 6

# EGGN307: Solving Differential Equations using Laplace

Transforms
Tyrone Vincent
Lecture 5

Contents
1

## Finding Solutions to Differential Equations

1.1 Partial Fraction Expansion . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
1.1.1 Partial fraction expansion - simple real poles . . . . . . . . . . . . . . . . . . . . . . . . . .
1.1.2 Partial fraction expansion - simple complex poles . . . . . . . . . . . . . . . . . . . . . . . .

1
2
3
4

Quiz Yourself
2.1 Questions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
2.2 Solutions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .

5
5
6

## Finding Solutions to Differential Equations

As promised, we can now solve differential equations using Laplace Transforms. What we do is transform the differential equation into an algebratic relation using Lapalce Transforms, solve for the Laplace Transform of the solution,
then use inverse Laplace Transforms to bring the solution back into the time domain. The most important property of
the Laplace transform in this case is the differentiation property:


d
L
f (t)
= sF (s) f (0 ),
dt
 2



d
d
df
L
f
(t)
=
sL
f
(t)
(0 ),
dt2
dt
dt
df
= s2 F (s) sf (0 ) (0 ),
dt
 n

d
n
n1

L
f (t)
= s F (s) s
f (0 )
dtn
sf (n2) (0 ) f (n1) (0 ).
A good starting point to remember this is: if the initial conditions are zero, we can replace nth order differentiation
with sn . Note that because we have defined the Laplace Transform with the lower limit of integration zero, we must
always take the starting time as 0, which is no problem for linear constant coefficient differential equations.
Example 1. Here is a simple differential equation:
dx
= 1 t 0.
dt

Commons, 171 Second Street, Suite 300, San Francisco, California, 94105, USA.

What is x(t)? Since the functions are equal on the left and right, the Laplace Transforms will be equal:
sX(s) x(0 ) =

1
.
s

## Solve for X(s) :

x(0 )
1
+
.
s2
s
We recognize the Laplace Transforms on the right hand side, resulting in the solution
X(s) =

x(t) = t + x(0 ) t 0.
Example 2. Lets find the trajectory for a mass spring damper system subject to an initial condition and an applied
force.
Mass-spring-damper System
f (t)

## At time t = 0, this system is at position x = 0,

but with an initial velocity of 1 m/s. Beginning
at this time, the force f (t) = e3t is applied.
Find x(t) for t 0.
3

x
+ 3x + 2x = e3t

x(0) = 0, x(0)

= 1.

## Taking the Laplace Transform of both sides:


s2 X(s) 1 + 3sX(s) + 2X(s)


s2 + 3s + 2 X(s)

X(s)

=
=

1
,
s+3
1
s+4
+1=
,
s+3
s+3
s+4
,
2
(s + 3s + 2)(s + 3)
s+4
.
s3 + 6s2 + 11s + 6

This the Laplace Transform of the trajectory, but what is the inverse Laplace Transfom? We need to break this rational
function up into parts that we can recognize by using partial fraction expansion. This is covered in the next section.

1.1

## Partial Fraction Expansion

We can use a partial fraction expansion to break a rational function up into easily recognizable parts. For example, we
can determine from observation that the inverse Laplace transform of
X(s) =
2

3
s5

is given by
x(t) = 3e5t .
The partial fraction expansion method is best described using an example, but there are several possible different cases.
1.1.1

## Example 3. Find the inverse Laplace Transform of

X(s) =

s+4
.
s3 + 6s2 + 11s + 6

Solution: In order to apply the partial fraction expansion, we must first find the roots of the denominator, which
are 1, 2, and 3. We can rewrite X(s) as
X(s) =

s+4
.
(s + 1)(s + 2)(s + 3)

Since all the roots are real and simple (not multiple) we look for a partial fraction expansion of the form
X(s) =

A
B
C
+
+
.
s+1 s+2 s+3

All that is left is to find the values of the unknown coefficients A, B, C,which are called residues. There are several
ways to do this:
Method 1: Equating coefficients Since we need the two representations to be equal, we have
s+4
A
B
C
=
+
+
.
(s + 1)(s + 2)(s + 3)
s+1 s+2 s+3
Putting the right hand side under a common denominator,
s+4
A(s2 + 5s + 6) + B(s2 + 4s + 3) + C(s2 + 3s + 2)
=
.
(s + 1)(s + 2)(s + 3)
(s + 1)(s + 2)(s + 3)
Equating coefficients gives us the three equations
A+B+C

0,

5A + 4B + 3C

1,

6A + 3B + 2C

4.

Solving for A, B, C :
A =

1.5,

2,

0.5.

so

1.5
2
0.5
+
+
.
s+1 s+2 s+3
and we can easily find the inverse Laplace Transform as
X(s) =

## x(t) = 1.5et 2e2t + 0.5e3t .

Method 2: Finding residues directly We again start with the funamental desired equality
X(s) =

A
B
C
s+4
=
+
+
.
(s + 1)(s + 2)(s + 3)
s+1 s+2 s+3

## Now, if we multiply both sides by (s + 1), we get

(s + 1)X(s) =

(s + 1)B
(s + 1)C
s+4
=A+
+
.
(s + 2)(s + 3)
s+2
s+3

Letting s = 1,
3
= A + 0 + 0.
12
We have found an equation for A! Clearly, A = 1.5, as we saw before. In general, to find the residue of a simple
pole pi , multiply the rational function by (s pi ) and let s = pi , the result is the residue. We find
(s + 1)X(s)|s=1 =

2
= 2,
(1)(1)
1
=
= 0.5.
(2)(1)

(s + 2)X(s)|s=2 =

(s + 2)X(s)|s=3

as expected.
1.1.2

## Partial fraction expansion - simple complex poles

Fundamentally, simple complex poles can be dealt with in the same way as simple real poles. However, it is useful to
keep complex conjuate poles together
Example 4. Find the inverse Laplace Transform of
F (s) =

3s2 + 10s + 10
.
s3 + 4s2 + 6s + 4

In this case, the roots of the denominator are 2, 1 + j, 1 j. We could break this up into three terms as before,
but it is easier to keep the complex conjugate poles together, so we want to find the following expansion:
F (s) =

A
Bs + C
+ 2
.
s + 2 s + 2s + 2

The complex conjugate term must have Bs + C in the numerator in order to be assured of a solution. We can find A
using the direct residue method:

3s2 + 10s + 10
12 20 + 10
2
A = (s + 2)F (s)|s=2 =
=
= = 1,

2
s + 2s + 2 s=2
44+2
2
while B and C can be found by equating coefficients, or by our third method of finding residues:
Method 3: Equating coefficients for certain values of s So far, we have
F (s) =

3s2 + 10s + 10
1
Bs + C
=
+
.
+ 4s2 + 6s + 4
s + 2 s2 + 2s + 2

s3

Since this equaltiy must hold for all values of s, it must hold for particular values of s that we choose. If s = 0
is not a pole, then this is a good choice to plug into both sides. We get
2

3 (0) + 10 (0) + 10
3

1
B (0) + C
,
+
0 + 2 (0)2 + 2 (0) + 2
1 C
=
+ ,
2
2
= C,
=

10
4
4
4

## giving us C dircetly. Plugging s = 1 into both sides, we get

2

1
B (1) + C
,
+
1 + 2 (1)2 + 2 (1) + 2
1 B+C
=
+
,
3
5
= B + C,

3 (1) + 10 (1) + 10
3

## (1) + 4 (1) + 6 (1) + 4

23
15
6
or B = 6 4 = 2.
This gives us

1
2s + 4
+ 2
.
s + 2 s + 2s + 2
The final step is to find the inverse Laplace Transform. The first term is easy, as we recognize it as an exponential. For
the second term, we need to look at the transform pairs that involve complex conjugate roots:
F (s) =

sine

sin t

cosine

cos t

damped sine

eat sin t

damped cosine

eat cos t

s2 + 2
s
s2 + 2

(s+a)2 + 2
s+a
(s+a)2 + 2

First, we should put the denominator into the form (s + a)2 + 2 by completing the square
s2 + 2s + 2

s2 + 2s + 1 + 1,

(s + 1) + 1.

## Then, we need to put the numerator into the correct form,

2s + 4 = 2(s + 1) + 2
so we have

2s + 4
(s + 1)
1
=2
+2
,
(s + 1)2 + 1
(s + 1)2 + 1
(s + 1)2 + 1

or
F (s) =

1
(s + 1)
1
+2
+2
,
s+2
(s + 1)2 + 1
(s + 1)2 + 1

and
f (t) = e2t + 2et cos(t) + 2et sin(t),
by inspection.

Quiz Yourself

2.1

Questions

(a) F (s) =

3s+1
s(s+1)(s+2)

(b) F (s) =

3s+1
s(s2 +4s+4)

2.2

Solutions

1.
(a)

(b)